PEMANFAATAN KOLAGEN DARI HEWAN - Retna Ayu Septiani; Dinda Aisyah; Sylva Ayu Widya Cahyati; Farid Ahmad; Neni Sri Gunarti (Jurnal Buana Farma, 2023)
The use of animals is not only used as a raw material for food, but on the other hand it turns out that animals can be used as important biomaterials for medical applications such as collagen. This review article discusses the utilization of collagen from various types of animals according to the relevant parameters. Article reviews are expected to provide scientific information about the various types of collagen in animals. The method used is literature study by looking for several different journal sources. The inclusion data used in this review are journals for the last 10 years (2012-2022). Collagen is usually found in the skin of cows and pigs, but these two animals are still a problem in Indonesia. Apart from these two, collagen can also be found in mammals such as buffalo and chickens, but they need to be slaughtered to get the halal aspect. Collagen can also be found in marine life such as sea urchins, tuna, catfish, skipjack tuna, sea catfish, milkfish, tilapia, machete fish, cod, green mussels, blood clams, and gamma sea cucumbers.